A systematic review investigating the use of Twitter and Facebook in university-based healthcare education. Issue 5 (29th July 2014) - Smith, Toby; Lambert, Rodney
Abstract : Purpose: – The purpose of this paper is to evaluate the use, attitudes and perceptions of both teachers and students towards social media platforms (Facebook and Twitter) in healthcare higher education practice. Design/methodology/approach: – Systematic literature review. A search of published and unpublished databases was conducted from January 2000 to January 2013. Data were synthesised through a narrative approach. All included studies were critically appraised using Critical Appraisal Skills Programme appraisal tools. Findings: – From a total of 876 papers, 16 publications met the eligibility criteria. The review papers were largely of moderate methodological quality. The results indicated that Facebook and Twitter are perceived as potentially useful adjuncts in healthcare higher education practice. Their use as part of a "blended" approach to classroom teaching has been employed to enhance communication and increase accessibility of students to real-world practices and expertise. Whilst students perceive this to be of value, some have reservations regarding the possibility of faculty members spying or infringing on their "virtual" social community. Faculty members expressed some reservations regarding the perceived boundary between student-staff relationships. Originality/value: – This is the first paper to systematically review the literature on the use of social media networking sites in health education. This identified both the potential strengths and weaknesses of using this new technology, and highlights areas to expand knowledge with further research and practice.